Design, Modelling, Control and Simulation of Biomimetic Underwater Robot - Mayz, Oscar; Sanoja, Carlos; Certad, Novel (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS), 2019)
Inspired by the efficiency and versatility of fish swimming, a field arises which involves vehicles with designs biologically based or biomimetic. This kind of design replicates the characteristics of the anatomy of aquatic species, in order to take advantage of the benefits associated with higher performance at lower speeds and improved maneuverability. This paper presents the model of a bioinspired underwater vehicle. An optimization algorithm (PSO) is used to find the dimensions of the prototype, taking into account certain constraints. A CAD is simulated in fluid to obtain an estimate of the forces and the drag coefficient. Two dynamic models are established, one LTI and one Non-linear based on the dynamics of conventional submarines, but with propulsion inspired by the kinematics equation of the carangiform swimmer.